Age-specific features of soccer players' heart dimensions - Olm, T.; Baskin, K.; Herde, K. (American Journal of Sports Science, 2017)
This work concentrates on the analysis of the echocardiographic part of our complex investigation which determined the characteristics of work capacity, the cardio-respiratory system and the nervous system. Professional healthy male soccer players of the best clubs of Estonia (n=236) aged 17 to 31 years were examined. Athletes were divided into three age groups. All tests were performed in the same training period. The statistical analysis of all characteristics (ANOVA-test, Pearson product moment correlation) allows us to conclude that the character of heart development depends on age. Soccer`s sport-specific effect on heart produces an adaption where both the dilatation and the wall thickening of the heart occur moderately but not at the same time.